Studies on economic well-being essays in the honor of John P. Formby - Bishop, John A.; Amiel, Yoram (Emerald, 2004)
Research on Economic Inequality, Volume 12 is the outgrowth of University of Alabama Poverty and Inequality conference, May 22-25, 2003. The motivation for the conference was to honor John P. Formby upon his retirement. The conference, funded by the University, was designed to bring together three groups of people; first, some of the most recognized scholars in the field, second, current and former colleagues of John Formby's working in this field, and third, Dr. Formby's former PhD and post-doctoral students. Seventeen papers were presented, eleven of which are authored or co-authored by Dr. Formby's former students. Peter Lambert and Yoram Amiel also participated in the conference. Dan slottje, John Creedy, Shlomo Yitzhaki and Quentin Wodon did not attend but contributed papers.The first two papers in Volume 12 examine the impact of the minimum wage. The Formby-Bishop-Kim paper compares the poverty reducing effects of the minimum wage to two alternative poverty reducing policies. In the Cover-Kim paper, the authors control for local cost of living to gauge the impact of the minimum wage on teenage employment. The third and fourth papers apply experimental methods to study respondent's attitudes toward inequality and risk. The Beckman et al. paper asks whether the failure to reliably observe inequality aversion (in experiments) extends to risk aversion. In the fifth paper, Buhong Zheng investigates the properties of intermediate measures of inequality. The paper questions, whether these measures maintain their intermediateness through inequality neutral transformations, and the unit consistency of these measures.In the sixth paper, Bishop-Chow-Zeager extend their earlier work on Lorenz curve decompositions. The decomposed Lorenz curve can be easily used to construct interdistributional Lorenz curve measures of economic advantage among subgroups. Using U.S. data they find smaller economic advantages over time by race and region, although not by marital status. In the seventh paper, Yitzhaki and Wodon observe that mobility is the transition between two inequality states and establish the equivalence of the Gini index with the Atkinson-Plotnik measure of horizontal equity. They illustrate their results with data from rural Mexico. The eighth and ninth papers address tax microsimulation modeling. Creedy-Kalb-Scutella compare alternative approaches to measuring poverty and inequality in a discrete hours model.
Keywords: Formby, John P.; Business & Economics -- Economics -- Microeconomics.; Economics.; Income distribution -- Congresses.; Poverty -- Congresses.; elektronické knihy; electronic books